Analysis of market behavior in Farmer´s Markets located in the Greater Metropolitan Area - García-Barquero, Manuel Enrique (2016)
A study was conducted in order to analyze the market behavior of farmer´s markets in the Greater Metropolitan Area, taking into account the legal regulations of these markets and marketing theory to determine the way in which these markets develop, through the variables of supplier participation, regular clients per supplier and regular clients per product. Considering these variables, the way in which farmers plan the supply of agricultural products was determined: 80% of participants sell between 84 and 100% of weakly supply. It is important to mention that for the analysis of this study, the 20 main horticultural and fruit products with higher volume of commercialization in the National Center for Food Supply and Distribution (CENADA) were used. Of these, 18 products held a constant participation, which varies between 50 and 83% in a year, however, mangoes and watermelons held a lower percentage due to production seasonality.